Measurement of Optic Nerve Sheath Diameter Using Ultrasound as an Indicator of Raised Intracranial Pressure in Patients with Pre-Eclampsia (Nepalese Journal of Radiology, 2025)
Introduction: Preeclampsia is one of the common complications of pregnancy which may have life- threatening complications. One of the main neurological consequences of preeclampsia includes increased intracranial pressure (ICP), which can be demonstrated by an increase in optic nerve sheath diameter (ONSD). The usefulness of transorbital ultrasound (USG) to assess ONSD has seldom been sought in our practice. This study aims to measure ONSD in individuals with preeclampsia and compare it with that of healthy pregnant females.Methods: This prospective, randomized comparative study was performed on 60 patients and the individuals were categorized into three groups; Group I- normal pregnancy (N=20), Group II -mild preeclampsia (N=20), and Group III- severe preeclampsia group (N=20). Using a high-resolution linear ultrasound probe ONSD was measured 3mm behind the globe, and the values were compared with normal pregnant females as controls.Results: The three groups were comparable in terms of age, gestational age, gravidity, and weight. The ONSD was notably elevated in patients with preeclampsia in comparison to the control group (p